2021
DOI: 10.1186/s12909-021-02575-1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study regarding distance learning and the conventional face-to-face approach conducted problem-based learning tutorial during the COVID-19 pandemic

Abstract: Background Educational pedagogies were modified during the COVID-19 pandemic to minimise interruption to teaching. One approach has been the distance learning problem-based learning (PBL) tutorial utilising the online peer-to-peer platform. The aim of this study was to compare the performance of students using distance learning PBL tutorials using with that of students utilising the conventional face-to-face approach. Methods This retrospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 18 publications
5
111
0
10
Order By: Relevance
“…That is, whereas some studies reported that this transition was associated with an improved mood and academic functioning [5,[11][12][13][14], other studies reported increased distress, decreased well-being and a worsened academic performance after the transition [2,3,6,8,9,15,16]. An experimental study comparing face-to-face and online problembased learning sessions suggests that poorer online academic performance during lockdown is related to decreased participation, communication, preparation, critical thinking and group skills [16]. Another factor that seems to negatively impact academic performance is the lack of structure and routine [15].…”
Section: Discussionmentioning
confidence: 99%
“…That is, whereas some studies reported that this transition was associated with an improved mood and academic functioning [5,[11][12][13][14], other studies reported increased distress, decreased well-being and a worsened academic performance after the transition [2,3,6,8,9,15,16]. An experimental study comparing face-to-face and online problembased learning sessions suggests that poorer online academic performance during lockdown is related to decreased participation, communication, preparation, critical thinking and group skills [16]. Another factor that seems to negatively impact academic performance is the lack of structure and routine [15].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the delayed graduations, especially in medical education, may have negative impacts, especially in this pandemic management setting. Therefore, educational methods have been shifting to online approaches [ 2 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is oriented towards questions and problems that train creative thinking skills so that students are more focused on determining the problems sought through experiments and understanding physics concepts through actual experiments. If professional teachers apply PBL learning, it is suspected that the three dependent variables, namely the value of learning achievement, critical thinking skills, and creative students taught by PBL, will be higher than the scores of students with conventional learning (Foo et al, 2021).…”
Section: Resultsmentioning
confidence: 99%